2017
DOI: 10.5365/wpsar.2017.8.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Establishing seasonal and alert influenza thresholds in Cambodia using the WHO method: implications for effective utilization of influenza surveillance in the tropics and subtropics

Abstract: ObjectiveTo establish seasonal and alert thresholds and transmission intensity categories for influenza to provide timely triggers for preventive measures or upscaling control measures in Cambodia.MethodsUsing Cambodia’s influenza-like illness (ILI) and laboratory-confirmed influenza surveillance data from 2009 to 2015, three parameters were assessed to monitor influenza activity: the proportion of ILI patients among all outpatients, proportion of ILI samples positive for influenza and the product of the two. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 27 publications
6
41
0
Order By: Relevance
“…Our data concur with the findings from previous studies describing the seasonal circulation of influenza viruses in Cambodia with year‐round co‐circulation of multiple influenza subtypes . Influenza viruses detected in Cambodia continued to be susceptible to oseltamivir and zanamivir, but resistance to adamantanes was still universal in influenza A viruses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data concur with the findings from previous studies describing the seasonal circulation of influenza viruses in Cambodia with year‐round co‐circulation of multiple influenza subtypes . Influenza viruses detected in Cambodia continued to be susceptible to oseltamivir and zanamivir, but resistance to adamantanes was still universal in influenza A viruses.…”
Section: Discussionsupporting
confidence: 91%
“…Future policies for the introduction of seasonal vaccination in Cambodia will be aided by the distinct seasonality of influenza circulation, which is unusual for a tropical country, and should be aligned with a vaccination program mirroring the WHO southern hemisphere vaccination formulation timetable with vaccinations ideally taking place in March‐April. Recent introduction of seasonal alert thresholds in Cambodia using the “WHO method” will also help to refine the ideal vaccination timing.…”
Section: Discussionmentioning
confidence: 99%
“…β( t ) is the transmission coefficient, representing the probability of transmission per contact between an infected and a susceptible individual. As influenza transmission intensity changed during an epidemic season and the duration of each intensity varied, we assumed different values of β corresponding to three different infectious times in this study. σ is the rate at which an exposed individual becomes infectious per unit of time.…”
Section: Methodsmentioning
confidence: 99%
“…Cambodia has conducted influenza surveillance since 2009, including both outpatient influenza‐like illness surveillance and hospitalized SARI surveillance, and enrolls all patients meeting the Cambodia SARI case definition at eight sentinel surveillance sites. Surveillance has demonstrated that influenza viruses commonly circulate during the rainy season (June‐November) in Cambodia each year 13, 14. Between 2009 and 2014, influenza circulation peaked between August and November; influenza positivity among SARI cases fluctuated from 12% in 2009 to 3% in 2014 15…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance has demonstrated that influenza viruses commonly circulate during the rainy season (June-November) in Cambodia each year. 13,14 Between 2009 and 2014, influenza circulation peaked between August and November; influenza positivity among SARI cases fluctuated from 12% in 2009 to 3% in 2014. 15 To better understand the impact of influenza on the Cambodia population and inform possible future vaccine policy, health officials are exploring best practices to estimate the burden of influenzaassociated SARI in the country.…”
Section: Introductionmentioning
confidence: 99%